PERGESERAN DAN PERUBAHAN MAKNA KATA سَيَّارَةٌ DALAM AL-QURAN - Faridl Hakim (Tazkiya, 2017)
This article discuss the meaning of sayyarah in the Qur'an. The theory that have been used historical semantic theory. Historical semantics is the study of meaning in terms of the history of the language or word. The results of this study was first sayyarah used in the Qur'an in several verses. Both words sayyarah experience shifts and changes in a different context, according to the needs of speakers of language, the aspects of both linguistics are widespread, narrow or balance.